Brain Citrullination Patterns and T Cell Reactivity of Cerebrospinal Fluid-Derived CD4+ T Cells in Multiple Sclerosis - Faigle, Wolfgang; Cruciani, Carolina; Wolski, Witold; Roschitzki, Bernd; Puthenparampil, Marco; Tomas-Ojer, Paula; Sellés-Moreno, Carla; Zeis, Thomas; Jelcic, Ivan; Schaeren-Wiemers, Nicole; Sospedra, Mireia; Martin, Roland (Frontiers in Immunology, 2019)
Abstract Immune responses to citrullinated peptides have been described in autoimmune diseases like rheumatoid arthritis (RA) and multiples sclerosis (MS). We investigated the post-translational modification (PTM), arginine to citrulline, in brain tissue of MS patients and Controls (C) by proteomics and subsequently the cellular immune response of cerebrospinal fluid (CSF)-infiltrating T cells to citrullinated and unmodified peptides of myelin basic protein (MBP) and glial fibrillary acidic protein (GFAP). With specifically adapted tissue extraction- and combined data interpretation protocols we could establish a map of citrullinated proteins by identifying more than 80 proteins with two or more citrullinated peptides in human brain tissue. Many of them we report for the first time. For the already described citrullinated proteins MBP, GFAP and vimentin, we could identify additional citrullinated sites. The number of modified proteins in MS white matter was higher than Control tissue. Citrullinated peptides are considered neoepitopes that may trigger autoreactivity. We used newly identified epitopes and previously reported immunodominant myelin peptides in their citrullinated and non-citrullinated form to address the recognition of CSF-infiltrating CD4+ T cells from 22 MS patients by measuring proliferation and IFN- secretion. We did not detect marked responses to citrullinated peptides, but slightly more strongly to the non-modified version. Based on these data, we conclude that citrullination does not appear to be an important trigger of a T cell response. Citrullination may not be the trigger but the consequence of an immune response. Our approach allowed us to perform a deep proteome analysis and opens new technical possibilities to analyse complex PTM on minute quantities of rare tissue samples.